Study of The Decorative Diversity Elements on Buildings During The Socialist Period in Mongolia - Enkhbat, Shinezaya; Ariunbayar, Namuun; Baigalsaikhan, Baigal-Erdene; Azli, Mohd (MAJ - Malaysia Architectural Journal, 2025)
Mongolians are nomadic people, because of the extreme climate conditions, nomadic people were living in a nomadic lifestyle in the four seasons of the year. Nomadism has survived to this day and is a way of life in perfect harmony with nature. Therefore, the Nomadic Mongolian did not have the opportunity to build a city and live in a settled place, but due to the influence of Buddhism, the need for a settled life such as "khuree city" where the monasteries were created. Influenced by Buddhism, Mongolians began leading settled lives and establishing monasteries. This led to the rise of unique Mongolian architectural styles in the 17th century, marking the end of the Feudal era. The style further evolved and developed until the Socialist era (1921 to 1989), when buildings incorporated Soviet-style characteristics. In 1948, the first Mongolian architects were trained in the Soviet Union and initiated the construction of buildings in Mongolia. Although the buildings were constructed in the Soviet style, Mongolian architectural elements were incorporated. Traditional Mongolian motifs and ornaments were included into the Socialist buildings, reflecting earlier monasteries and totems used for both interior and exterior decorations. Mongolian design is rich in ornaments and motifs, each having its meaning. Their incorporation greatly enhanced the aestheticism of the buildings. There's substantial research on various architectural periods, but minimal study specifically on the decorative elements of Mongolia's Socialist-era buildings. There's a significant gap in knowledge about the impact of Mongolia's Socialist era on its culture, architecture, and the link between architecture and regional socio-economic statuses. Therefore, the aim of this research is to evaluate and comprehend the influence of the Socialist period on Mongolia's architectural styles with a focus on decorative diversity, and to study the correlation between architectural aspects and socio-economic statuses in different regions of the country. Field research with observations and photos will be used to collect primary data from Socialist-era architectural sites in Mongolia. Secondary data will come from academic articles, history records, and archives. Data will be analyzed qualitatively, categorizing decorative elements by form, material, and motifs. The association between these features and socio-economic factors will be examined using correspondence analysis. The study's findings and results will be finalized post-study. The aim is to gain insights into the diverse decorative elements and their significance during Mongolia's Socialist period. The conclusion will summarize the study's main findings, emphasizing the importance of architectural diversity in Mongolia's Socialist period and its links with socio-economic conditions. Future studies could look at how these buildings are preserved or compare Mongolia's Socialist-era architecture with similar periods worldwide to better understand cultural and political impacts on architecture.